The duke heist - Ridley, Erica (Ridley, Erica. Wild Wynchesters, 2021)
Chloe Wynchester is completely forgettable -- a curse that gives her the ability to blend into any crowd. When the only father she's ever known makes a dying wish for his adopted family of orphans to recover a missing painting, she's the first one her siblings turn to for stealing it back. No one expects that in doing so, she'll also abduct a handsome duke. Lawrence Gosling, the Duke of Faircliffe, is tortured by his father's mistakes. To repair his estate's ruined reputation, he must wed a highborn heiress. Yet when he finds himself in a carriage being driven hell-for-leather down the cobblestone streets of London by a beautiful woman who refuses to heed his commands, he fears his heart is hers. But how can he sacrifice his family's legacy to follow true love?